Influence of visual merchandising, creative promotion, and price on purchase decisions in live shopping Shopee - Darma, Andrian Mulya; Napitupulu, Elfrida Viesta (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2024)
Indonesia's internet boom (212.9 million users) fueled e-commerce growth, with Shopee leading the market (158 million visitors). This study explored factors influencing purchase decisions in Jakarta's Shopee live shopping. Live streams offered product visualization, seller interaction, and promotions. We investigated how visual merchandising, creative promotions, and price impacted buying decisions through a survey of 462 respondents. The research found that creative promotions and price significantly influenced purchases, while visual merchandising had no effect.